Sociolinguistic Analysis of School Failure among High School Students - Rachida Bounhir (Journal of Educational and Human Sciences, 2021)
School failure has been a subject of numerous studies for decades. Many researchers have conducted studies to investigate the causes of this failure. Some have attributed this failure to families and insist that they have to hold the responsibility for the success or failure of their childrenThe purpose of this study is to record the beliefs/views of teachers and students on the sociolinguistic factors of school failure. The facts of this research are part of a wider research concerning student’s social adequacy having used a questionnaire and the viability of the educational system. The sample used for this research was 30 pupils and 20 teachers from Marrakesh. The results show that both teachers and students attribute school failure to different sociological and psychological factors. Results and implications of this analysis will be presented at the end of this paper. Some recommendations are presented as well.